Нейромережне моделювання та оптимізація технологічних параметрів контактного точкового зварювання - Fedin, Sergey S.; Zubretska, Nataliia A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2020)
A method is proposed for establishing the optimal values of technological process parameters when solving the inverse multivariate regression problem based on neural network modeling and the simplex search algorithm. The practical application of the method is implemented using the contact spot welding process as an example. It aims to optimize the design parameter – the core diameter of welded joints to reduce their defects during serial production.